Excess mortality and associated community risk factors related to hurricane Maria in Puerto Rico - Kristen N Cowan; Diego E Zavala; Erick Suarez; José A Lopez-Rodriguez; Omar Alvarez (Environmental Research: Health)
Background: In the 6 months following Hurricane Maria the number of people who died from the hurricane was much higher than was initially estimated from death certificates. Disruption of health care services and displacement led to the exacerbation of pre-existing chronic diseases. The objectives of this study were to (1) estimate the excess deaths in Puerto Rico in the 6 months following Maria, (2) identify geographical areas experiencing higher risk of chronic disease mortality following Maria and (3) identify community-level vulnerability characteristics associated with some communities being at higher risk of increased chronic disease mortality after Maria. Methods: Death records were obtained from Puerto Rico’s Department of Health Demographic Registry. Mortality risks per 100 000 were calculated for chronic disease categories and all-cause mortality for the 6 months following Maria and the same months in the year before. Geospatial analysis using Getis–Ord Gi* Statistic was used to determine if mortality clusters of 6 month mortality risk following hurricane Maria by census tract were statistically significant. Multinomial logistic regression was used to model the association between census tract level social vulnerability and being classified as higher or sustained risk of mortality in the 6 months following Hurricane Maria compared to the previous year’s mortality risk. Odds ratios and 95% confidence intervals were estimated to measure associations between social vulnerability and mortality risk. Results: In the 6 months following Maria there were increases in mortality risk for cardiovascular disease, Alzheimer’s, diabetes, sepsis, chronic respiratory disease, hypertension and all-cause mortality. Examining community level characteristics associated with vulnerability to disasters, neighborhoods with higher proportion of people 65 and older, higher proportion of houses being multiunit structures and higher proportion of households with no vehicle, in comparison to other neighborhoods in Puerto Rico,were more likely to have sustained high risk for mortality before and after Maria or increased risk of being a hot spot for chronic disease mortality after Maria.